Effect of Scirpus grossus fiber density on acoustic absorption characteristics for insulation use - Suhaeri, Suhaeri; Husaini, Husaini; Dirhamsyah, Muhammad; Hasanuddin, Iskandar; Tajuddin, Tajuddin (Jurnal Polimesin, 2025)
Noise control is essential for achieving comfortable living and working environments. Natural fibers such as Scirpus Grossus offer a sustainable approach for sound absorption applications. This study investigates the effect of varying fiber densities of Scirpus grossus on sound absorption performance. Test specimens were fabricated at three density levels; 636.9 kg/³, 318.5 kg/m³, and 212.3 kg/m³. Each had a fixed mass of 50 grams, a diameter of 100 mm, and varying thicknesses of 10 mm, 20 mm, and 30 mm. The samples were hot-pressed at 200°C for 10 minutes. Sound absorption coefficients (SACs) were measured using a Brüel Kjær Impedance Tube Type 4206, following the transfer function method (ISO 10534-2:1998) over third-octave bands. The results show that fiber density significantly affects the sound absorption coefficient (SAC). A decrease in density to 212.3 kg/m³ led to a SAC increase of 0.12 points (approximately 20% relative to the initial SAC value of 0.5428 at 636.9 kg/m³), particularly at 4000 Hz. This indicates that lower-density samples exhibit better acoustic absorption behavior. The average Noise Reduction Coefficient (NRC) across all samples was around 45%, confirming their effectiveness in sound control. Based on SAC values, the samples are classified as Sound Absorption Class D. These findings suggest that Scirpus grossus fiber mats have strong potential for eco-friendly acoustic insulation materials, suitable for applications in building panels or vehicle interiors.